Promoting health in schools: theoretical reflections on the settings approach versus nudge tactics - Ewert, Benjamin (Social theory & health, 2017)
This paper compares and contrasts two different concepts of health promotion in schools from a theoretical perspective: on the one hand, nudge tactics seeking to change both students’ eating behaviour and their exercise routine and, on the other hand, the settings approach which focuses on the social determinants of health. After assessing both concepts critically, it is argued that nudge has three drawbacks in comparison to setting-based health promotion: Firstly, in primarily focussing on individual choices, nudge exclusively promotes students’ behavioural prevention while disregarding measures of structural prevention. Secondly, choice architects (nudgers) are likely to enforce cultural homogeneity when defining the meaning of school health, i.e. the right food or dose of exercise, while deviating lifestyles are implicitly judged to be irrational and unhealthy. Thirdly, within a nudge-based approach students are predominantly addressed as consumers (nudgees), while less attention is paid to other social identities such as citizens or co-producers. By investigating the examples of smart lunchrooms and an environment encouraging activity, it is demonstrated that nudge is not perceived as a deliberative and context-bound process but instead displays a selective focus on health issues. Due to these significant concerns, it is concluded that - despite its practical shortcomings - setting-based health promotion is superior to nudge - especially in schools.
Gesehen am 09.11.2018